Internet and Farmers Wellbeing: Evidence from Indonesia - Sugiharti, Rr. Retno; ABDULAH, RUSLI; Rahmayani, Dwi; Eka Asmarani, Tuti (MIMBAR : Jurnal Sosial dan Pembangunan, 2024)
This study aims to investigate the impact of internet usage types on the welfare of farmer households, focusing specifically on the distinction between internet use for trade and non-trade activities. Using Ordinary Least Squares (OLS) regression analysis on data from the 2020 SUSENAS (National Socioeconomic Survey) household survey, the study examines farmer households where the head of the household has internet access. The analysis explores how different uses of the internet correlate with household well-being and economic outcomes. The findings indicate that farmer households with internet access exhibit significantly higher welfare levels compared to those without internet. Notably, farmer households using the internet for commercial purposes—such as selling and purchasing goods or services—enjoy a marked improvement in welfare compared to those who only use the internet for non-trade activities. Households that access the internet solely for activities like reading news, social media browsing, or exchanging emails tend to experience lower welfare levels relative to those engaging in trade-related online activities. This study highlights the importance of promoting digital trade literacy and enabling rural internet infrastructure to maximize the potential benefits of internet access in farming communities. By understanding how internet access types impact farmer welfare, policymakers can better support the digital transformation of rural areas, aiming to improve socioeconomic conditions through targeted interventions. This research underscores the transformative potential of internet access when harnessed for trade purposes, offering valuable insights for rural development strategies.